Plasma-enhanced Ag-coated AgCl / 4, 5-dibromofluorescein composite photocatalyst and preparation method thereof

By growing Ag@AgCl on the surface of 4,5-dibromofluorescein nanosheets, a composite photocatalyst was formed, which solved the problems of narrow photoresponse range and low activity of traditional photocatalytic materials, and achieved efficient photocatalytic hydrolysis and stable hydrogen production sex.

CN119186647APending Publication Date: 2024-12-27DALIAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411601244.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The intrinsic band gap of traditional inorganic semiconductor photocatalytic materials is wide, resulting in a narrow light response range, limiting the improvement of the conversion efficiency of light energy to chemical energy. Pure 4,5-dibromofluorescein is low in solubility in aqueous media and photogenerated electrons. The poor separation efficiency from holes limits its photocatalytic activity.

Method used

By growing Ag@AgCl on the surface of 4,5-dibromofluorescein nanosheets, the visible light absorption is enhanced by the surface plasmon resonance effect, and the directional transfer of charge is promoted through the Schottky heterojunction structure to form Ag@AgCl/4,5 -Dibromofluorescein composite photocatalyst, the composite material was prepared by in-situ photodeposition method.

Benefits of technology

It significantly improves the visible light absorption capacity and photocatalytic activity of photocatalytic materials, broadens the light response range, improves the utilization rate of sunlight, and shows high efficiency and stability in the field of photocatalytic hydrolysis hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186647A_ABST
    Figure CN119186647A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of photocatalytic functional materials, and discloses a preparation method of a plasma enhanced Ag-coated AgCl / 4, 5-dibromofluorescein composite photocatalyst. According to the preparation method, Ag-coated AgCl is loaded on the surface of 4, 5-dibromofluorescein through an in-situ photodeposition method, and the Ag-coated AgCl / 4, 5-dibromofluorescein composite photocatalyst with the enhanced plasma is prepared. The excellent performance of the composite photocatalyst is prominently reflected as follows: firstly, Ag-coated AgCl generates a plasma resonance effect, and the light utilization efficiency and the energy conversion efficiency are improved by enhancing the local field intensity, resonance energy transfer, hot electron injection and other mechanisms; and secondly, a Schottky junction is formed between the Ag-coated AgCl and the 4, 5-dibromofluorescein, so that photon-generated carriers are effectively separated, the recombination probability of photo-generated electrons and holes is reduced, and the photocatalytic efficiency is improved. In addition, the invention also has the advantages of simple operation, simple preparation process, cheap and easily available raw materials and the like. The method plays a positive role in expanding and enhancing the types and sources of photocatalytic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photocatalytic functional materials, and specifically relates to an Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst and a preparation method thereof. Background Art

[0002] Photocatalytic hydrogen production technology plays an increasingly critical role in the development of today's zero-carbon energy field. However, traditional inorganic semiconductor photocatalytic materials generally have a wide intrinsic band gap and can only absorb high-frequency ultraviolet light and a part of high-energy photons in the visible light region, making the range of light response narrow, which seriously restricts the improvement of the efficiency of light energy to chemical energy conversion. Therefore, the development of new semiconductor photocatalytic materials that can capture a wide range of the solar spectrum has become the key to achieving efficient photocatalysis. Compared with inorganic photocatalytic materials, organic photocatalytic materials have many advantages such as excellent light capture ability, highly delocalized π electron structure, and easily adjustable molecular structure, and are therefore highly respected.

[0003] The organic semiconductor 4,5-dibromofluorescein has a large absorption cross section, high quantum efficiency and a wide range of light absorption. However, pure 4,5-dibromofluorescein has two shortcomings as a photocatalyst. First, in aqueous media, the solubility of 4,5-dibromofluorescein is low, resulting in a low density of surface active sites; second, the separation efficiency of photogenerated electrons and holes is poor, which leads to low photocatalytic activity. These problems greatly limit the practical application of 4,5-dibromofluorescein in the field of photolysis of water to produce hydrogen. Therefore, it is necessary to find a suitable modification method to improve its photocatalytic activity. Summary of the invention

[0004] The purpose of the present invention is to expand the diversity of photocatalytic materials, in particular to provide a Ag@AgCl / 4,5-dibromofluorescein composite photocatalytic material and a preparation method thereof, and to apply the material to the field of photocatalytic water decomposition to produce hydrogen.

[0005] The inventive concept of the present invention is that Ag@AgCl has a surface plasmon resonance effect, which can enhance the absorption of visible light. After combining with 4,5-dibromofluorescein with a wide light absorption range, it is expected to improve the visible light absorption capacity of semiconductor photocatalysts and reduce the recombination rate of photogenerated carriers, thereby achieving the purpose of improving the activity of photocatalytic materials. Based on this inspiration, the present invention has developed a Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst with visible light response and a preparation method thereof. The product of the present invention has the advantages of wide spectral response, high photocatalytic activity and good stability, and can be widely used in the field of photocatalytic hydrolysis and hydrogen production.

[0006] The photocatalyst of the present invention uses 4,5-dibromofluorescein nanosheets as carriers, and Ag@AgCl is grown on the surface of 4,5-dibromofluorescein nanosheets by in-situ photodeposition. The above-mentioned object of the present invention is achieved by the following technical solutions:

[0007] First, 4,5-dibromofluorescein was ultrasonically dispersed in deionized water to obtain suspension A;

[0008] Secondly, adding silver nitrate solution to suspension A under dark conditions to obtain solution B;

[0009] Again, sodium chloride solution was added to solution B and stirred in the dark to obtain solution C;

[0010] Finally, solution C was transferred to a quartz reactor and stirred under xenon lamp irradiation. After the reaction was completed, the solution was collected by centrifugation, washed, and dried to finally obtain x wt% Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst, wherein x represents the mass percentage of theoretical silver nanoparticles in 4,5-dibromofluorescein, and x=5-7.

[0011] Furthermore, the ratio of each component is: the volume ratio of silver nitrate to sodium chloride solution is 1.0:(2.2-2.8).

[0012] Preferably, the volume ratio of silver nitrate to sodium chloride solution is 1.0:2.5.

[0013] As a preferred embodiment of the present invention, the specific preparation method is:

[0014] S1: Weigh 100 mg of 4,5-dibromofluorescein into a beaker, add 30 ml of deionized water, and perform ultrasonic dispersion for 30 minutes to obtain a uniformly dispersed suspension A;

[0015] S2: In the dark, add 500-700 μl of silver nitrate solution to suspension A and stir for 30 minutes to obtain solution B; the silver nitrate solution is 0.0926 mol / L;

[0016] S3: 1250-1750 μl of sodium chloride solution was added to solution B, and stirred again in the dark for 30 minutes to obtain solution C; the sodium chloride solution was 0.0226 mol / L; and the volume ratio of silver nitrate to sodium chloride solution was 1.0:2.5.

[0017] S4: Transfer solution C to a quartz reactor and stir for 3 hours under xenon lamp irradiation; after the reaction is completed, collect the product by centrifugation, wash it with deionized water for 3 times, and finally dry the product collected by centrifugation in an oven for 12 hours to finally obtain x wt% Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst, wherein x represents the mass percentage of theoretical silver nanoparticles in 4,5-dibromofluorescein, and x=5-7.

[0018] The present invention also claims to protect the application of the above catalyst, especially the application in photocatalyst.

[0019] The specific method of this application is:

[0020] First, weigh 50 mg of Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst and put it into a 100 mg reactor, then add 50 ml of a mixed solution prepared by 40 ml of deionized water and 10 ml of triethanolamine. After sealing the reactor, evacuate the reaction system to a vacuum, then irradiate with a 300-watt xenon lamp with a 420-nanometer filter as the light source, turn on the gas circulation pump, and start the photocatalytic reaction under magnetic stirring. The sample is automatically injected once every hour during the reaction. Finally, the hydrogen content in the product is determined by gas chromatography to obtain the photocatalytic decomposition of water and hydrogen production results of the Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst.

[0021] The catalyst material can significantly improve the performance of decomposing water to generate hydrogen under visible light irradiation.

[0022] Compared with the prior art, the present invention has the following significant advantages:

[0023] (1) The present invention ingeniously uses the in-situ photodeposition method to prepare the Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst, accurately anchors the Ag@AgCl nanostructure on the surface of 4,5-dibromofluorescein, and successfully constructs an Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst with plasma enhancement effect. The method provided by the present invention does not require harsh reaction conditions such as high temperature and high pressure, and has significant advantages such as simple preparation method, cheap and easy to obtain raw materials, high experimental repeatability, and strong operability. As a new type of photocatalyst, this nanocomposite material not only exhibits strong photocatalytic performance, but also has excellent photocatalytic stability.

[0024] (2) The excellent performance of the Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst prepared by the present invention is mainly reflected in two aspects: First, Ag@AgCl has a plasma resonance effect. With the help of complex mechanisms such as the enhancement of local field strength, the efficient transfer of resonance energy and the effective injection of hot electrons, the efficiency of light energy capture and energy conversion can be greatly improved, and the absorption of visible light can be enhanced. After combining with 4,5-dibromofluorescein, the light response range of the composite system is further broadened, and the utilization rate of sunlight is greatly improved. Second, the Schottky heterojunction structure formed between the interface of Ag@AgCl and 4,5-dibromofluorescein can promote the directional transfer of charges, more effectively separate photogenerated carriers, and suppress the recombination probability of photogenerated electrons and holes, thereby showing a significantly enhanced photocatalytic activity.

[0025] In short, the present invention enriches the types and sources of visible light semiconductor catalytic materials, provides a new perspective and approach to solving energy problems, and also brings new breakthrough opportunities for the development of the field of photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A is a transmission electron micrograph of pure 4,5-dibromofluorescein;

[0027] Figure 1 B is the transmission electron microscopy image of Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst;

[0028] Figure 1 C is a comparison chart of the rates of hydrogen production from water decomposition by Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst, Ag@AgCl and pure 4,5-dibromofluorescein under visible light irradiation.

[0029] Figure 1 D is the cyclic stability diagram of the Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst for water decomposition and hydrogen production under visible light irradiation. DETAILED DESCRIPTION

[0030] In order to more clearly illustrate the purpose, technical solutions and advantages of the present disclosure, the embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings. It should be understood that the following description of the embodiments is intended to explain and illustrate the overall concept of the present invention, and should not be understood as limiting the present invention. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels.

[0031] Example 1

[0032] Step (1): First, weigh 100 mg of 4,5-dibromofluorescein, add 30 ml of deionized water, and disperse by ultrasonic for 30 minutes to obtain a uniformly dispersed suspension A.

[0033] Step (2): Then, 500 μL of silver nitrate solution (0.0926 mol / L) was added to the suspension A in the dark and stirred for 30 minutes to obtain solution B.

[0034] Step (3): Add 1250 μL of sodium chloride solution (0.0226 mol / L) (the volume ratio of silver nitrate to sodium chloride solution is 1.0:2.5) to solution B, and stir in the dark for another 30 minutes to obtain solution C.

[0035] Step (4): Solution C was transferred to a quartz reactor and stirred for 3 hours under xenon lamp irradiation. After the reaction was completed, the product was collected by centrifugation and washed with deionized water for 3 times. Finally, the product collected by centrifugation was placed in an oven and dried for 12 hours to finally obtain Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst with catalyst x=5.0.

[0036] Figure 1 (A) and (B) are transmission electron micrographs of pure 4,5-dibromofluorescein and Ag@AgCl / 4,5-dibromofluorescein composite photocatalysts, respectively. As shown in Figure (A), at a scale of 50 nm, the surface of 4,5-dibromofluorescein nanoparticles is relatively smooth, and the particle size is mostly concentrated around 50 nm. In Figure (B), it can be observed that 4,5-dibromofluorescein presents a flaky structure, with more Ag@AgCl dispersed on the surface of 4,5-dibromofluorescein, and the average particle size of Ag@AgCl is 30±5 nm.

[0037] Example 2

[0038] The difference between this embodiment and embodiment 1 is that the volumes of the silver nitrate solution and the sodium chloride solution added in step (3) are adjusted to 600 μl and 1500 μl, and finally the Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst with catalyst x=6.0 is obtained.

[0039] Example 3

[0040] The difference between this embodiment and embodiment 1 is that the volumes of the silver nitrate solution and the sodium chloride solution added in step (3) are adjusted to 700 μL and 1750 μL, and finally an Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst with catalyst x=7.0 is obtained.

[0041] Example 4

[0042] The difference between this embodiment and embodiment 1 is that the volume of the silver nitrate solution and the sodium chloride solution added in step (3) is adjusted to 0 μl, and the catalyst finally obtained is pure 4,5-dibromofluorescein.

[0043] First, weigh 500 mg of silver nitrate solid and 105.84 mg of sodium chloride solid, dissolve them in 25 ml of deionized water, and slowly add the prepared sodium chloride solution dropwise to the silver nitrate solution using a syringe pump (0.5 mL / min); then irradiate under a xenon lamp for 3 hours. Collect the precipitate by centrifugation, wash with deionized water, and finally vacuum dry at 60 degrees Celsius for 24 hours. The final product is Ag@AgCl.

[0044] Application Examples

[0045] The catalyst prepared in the embodiment of the present invention and pure 4,5-dibromofluorescein were used to perform an experiment of decomposing water and producing hydrogen under visible light irradiation.

[0046] The experimental steps are as follows:

[0047] First, weigh 50 milligrams of the Ag@AgCl / 4 obtained in Example 2, and the 5-dibromofluorescein composite photocatalyst is put into 100 milliliters of reactors, and 50 milliliters of mixed solutions prepared by 40 milliliters of deionized water and 10 milliliters of triethanolamine are added and the reactor is sealed. After the reaction system is evacuated to vacuum, a 300-watt xenon lamp equipped with a 420-nanometer filter is used as a light source for irradiation, and a gas circulation pump is turned on to carry out photocatalytic reaction under magnetic agitation, and automatic injection is performed once per hour during the reaction process. Finally, the product is measured and analyzed by gas chromatograph to obtain the photocatalytic decomposition of water and hydrogen production result of Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst. Simultaneously, the product obtained in Example 4 is used as a control sample, and experiments are carried out under the same conditions to obtain the photocatalytic hydrogen production result of 4,5-dibromofluorescein and Ag@AgCl.

[0048] Figure 1 (C) is a comparison of the rates of hydrogen production from water decomposition by Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst, Ag@AgCl, and pure 4,5-dibromofluorescein under visible light irradiation. From the comparison in the figure, it can be found that under visible light irradiation, the hydrogen production rate of Ag@AgCl is 0.00 μmol g -1 h -1 , that is, no hydrogen was produced, while the hydrogen production rate of Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst was as high as 2007.68 μmol g -1 h -1 This value is higher than that of pure 4,5-dibromofluorescein (39.73 μmol g -1 h -1) was 50.53 times higher than that of Ag@AgCl and pure 4,5-dibromofluorescein. Figure 1 (D) is a cyclic stability diagram of the Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst decomposing water to produce hydrogen under visible light irradiation. During the continuous irradiation of visible light for 20 hours, it can be observed that the hydrogen production activity of the composite photocatalyst has no obvious decay phenomenon. This result further proves that the photocatalytic material of the present invention has long-term stability in the process of photocatalytic hydrogen production.

[0049] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. Plasmon-enhanced Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst, characterized in that: Using 4,5-dibromofluorescein nanosheets as carriers, Ag@AgCl was grown on the surface of 4,5-dibromofluorescein nanosheets by in-situ photodeposition, and finally x wt% Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst was obtained, wherein x represents the mass percentage of theoretical silver nanoparticles in 4,5-dibromofluorescein, and x=5-7.

2. The method for preparing the composite photocatalyst according to claim 1, characterized in that: S1: ultrasonically dispersing 4,5-dibromofluorescein in deionized water to obtain a suspension A; S2: adding silver nitrate solution to suspension A in the dark to obtain solution B; S3: adding sodium chloride solution to solution B and stirring in the dark to obtain solution C; S4: Transfer solution C to a quartz reactor and stir it under the irradiation of a xenon lamp; after the reaction is completed, collect it by centrifugation, wash it, and dry it to finally obtain an xwt% Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst, wherein x represents the mass percentage of theoretical silver nanoparticles in 4,5-dibromofluorescein, and x=5-7.

3. The preparation method according to claim 2, characterized in that: The volume ratio of silver nitrate to sodium chloride solution is 1.0:(2.2~2.8).

4. The preparation method according to claim 3, characterized in that: The volume ratio of silver nitrate to sodium chloride solution is 1.0:2.

5.

5. The preparation method according to claim 2, characterized in that: The steps include: S1: Weigh 100 mg of 4,5-dibromofluorescein into a beaker, add 30 ml of deionized water, and perform ultrasonic dispersion for 30 minutes to obtain a uniformly dispersed suspension A; S2: In the dark, add 500-700 μl of silver nitrate solution to suspension A and stir for 30 minutes to obtain solution B; S3: Add 1250-1750 μl of sodium chloride solution to solution B, and stir again in the dark for 30 minutes to obtain solution C; S4: Transfer solution C to a quartz reactor and stir under the irradiation of a xenon lamp; after the reaction is completed, collect the product by centrifugation, wash it with deionized water for multiple times, and finally dry the product collected by centrifugation in an oven to finally obtain an x ​​wt% Ag@AgCl / 4,5-dibromofluorescein composite photocatalyst, wherein x represents the mass percentage of theoretical silver nanoparticles in 4,5-dibromofluorescein, and x=5-7.

6. The preparation method according to claim 5, characterized in that: In step S2, the silver nitrate solution is 0.0926 mol / L.

7. The preparation method according to claim 5, characterized in that: In step S3, the sodium chloride solution is 0.0226 mol / L.

8. The preparation method according to claim 5, characterized in that: In the step S4, stirring is performed for 3 hours under irradiation with a xenon lamp.

9. The preparation method according to claim 5, characterized in that: In step S4, the product is placed in an oven and dried for 12 hours.

10. The use of the composite photocatalyst according to claim 1, characterized in that: Under visible light, water is decomposed to produce hydrogen.